São Paulo’s strategic master plan and the challenges of sustainable urban transformation (Sustainability in Debate, 2021)
Cities play an essential role in the challenge of sustainability, and urban planning is one of the main tools for guiding urban transformation processes. This paper analyses the São Paulo Master Plan 2014, considering the principles and guidelines on compact cities, sustainable adaptation and ecosystem-based adaptation. An urban development model within sustainable parameters, however, involves conflict dynamics. In this sense, the views and demands of the main stakeholders seeking to influence the regulatory arena of São Paulo's urban policy are mapped. The analysis focuses on attempts to change the zoning law that would affect several of the definitions agreed in the Master Plan, prioritising mainly the interests of real estate developers.